Noise Levels of Multi-Rotor Unmanned Aerial Vehicles with Implications for Potential Underwater Impacts on Marine Mammals - Christiansen, Fredrik; Rojano-Doñate, Laia; Madsen, Peter T.; Bejder, Lars (Frontiers in Marine Science, 2016)
Despite the rapid increase in the use of unmanned aerial vehicles (UAVs) in marine mammal research, knowledge of the effects of UAVs on study animals is very limited. We recorded the in-air and in-water noise from two commonly used multi-rotor UAVs, the SwellPro Splashdrone and the DJI Inspire 1 Pro, to assess the potential for negative noise effects of UAV use. The Splashdrone and Inspire UAVs produced broad-band in-air source levels of 80 dB re 20µPa and 81 dB re 20µPa (rms), with fundamental frequencies centered at 60 Hz and 150 Hz. The noise of the UAVs coupled poorly into the water, and could only be quantified above background noise of the recording sites at 1m depth when flying at altitudes of 5 and 10m, resulting in broad-band received levels around 95 dB re µPa rms for the Splashdrone and around 101 dB re µPa rms for the Inspire. The third octave levels of the underwater UAV noise profiles are i) close to ambient noise levels in many shallow water habitats, ii) largely below the hearing thresholds at low frequencies of toothed whales, but iii) likely above the hearing thresholds of baleen whales and pinnipeds. So while UAV noise may be heard by some marine mammals underwater, it is implied that the underwater noise effect is small, even for animals close to the water surface. Our findings will be valuable for wildlife managers and regulators when issuing permits and setting guidelines for UAV operations. Further, our experimental setup can be used by others to evaluate noise effects of larger sized UAVs on marine mammals.